2020
DOI: 10.3390/microorganisms8030385
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Thermophilic Plant Biomass Hydrolysis from Caldicellulosiruptor Systems Biology

Abstract: Plant polysaccharides continue to serve as a promising feedstock for bioproduct fermentation. However, the recalcitrant nature of plant biomass requires certain key enzymes, including cellobiohydrolases, for efficient solubilization of polysaccharides. Thermostable carbohydrate-active enzymes are sought for their stability and tolerance to other process parameters. Plant biomass degrading microbes found in biotopes like geothermally heated water sources, compost piles, and thermophilic digesters are a common s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 145 publications
1
12
0
Order By: Relevance
“…This sugar preference pinpoints to an adaptation to a specific niche within the thermophilic lignocellulosic degradation community. Other such specialization within lignocellulosic degradation communities has been indicated before [ 23 ].…”
Section: Discussionsupporting
confidence: 58%
“…This sugar preference pinpoints to an adaptation to a specific niche within the thermophilic lignocellulosic degradation community. Other such specialization within lignocellulosic degradation communities has been indicated before [ 23 ].…”
Section: Discussionsupporting
confidence: 58%
“…This sugar preference pinpoints to an adaptation to a specific niche within the thermophilic lignocellulosic degradation community. Other such specialization within lignocellulosic degradation communities has been indicated before [26].…”
Section: Discussionmentioning
confidence: 70%
“…CP002219.1), and C. saccharolyticus DSM 8903 (accession no. CP000679.1) ( Van De Werken et al , 2008 ; Kataeva et al , 2009 ; Blumer-Schuette et al , 2011 ; Wai et al , 2015 ; Blumer-Schuette, 2020 ). NifN was not found in the genomes based on the annotation using eggNOG-mapper v2 ( Huerta-Cepas et al , 2017 ; 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“… Nishihara et al (2018c) also performed a nifH gene amplicon analysis of chemosynthetic microbial communities at temperatures between 72 and 77°C, and the findings obtained showed that the relative abundance of the nifH gene from Caldicellulosiruptor were 7.42, 48.97, 73.12, and 94.58% in the four samples analyzed. The genus Caldicellulosiruptor comprises thermophilic fermentative bacteria that exhibit cellulolytic activities ( Zverlov et al , 1998 ; Blumer-Schuette et al , 2012 ; Brunecky et al , 2013 ) and is widely distributed in globally diverse thermal environments ( Lee et al , 2018 ; Blumer-Schuette, 2020 ). Genes related to nitrogen fixation are found in the genomes of some species in this genus (CP002330.1, CP002326.1, CP002219.1, CP003001.1, CP000679.1, LACO01000001.1, LACM01000001.1, and LACN01000001.1); however, their nitrogenase activities and dinitrogen-dependent growth have not yet been demonstrated.…”
mentioning
confidence: 99%